2015
DOI: 10.1001/jamafacial.2014.1574
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Use of Dexamethasone in Rhinoplasty

Abstract: IMPORTANCE Postoperative edema and ecchymosis following rhinoplasty are a cause of anxiety for both patients and physicians and can affect the cosmetic results. Corticosteroids have been used to reduce these events. OBJECTIVE To determine whether preoperative use of dexamethasone sodium phosphate alters the occurrence of edema and ecchymosis following rhinoplasty. DESIGN, SETTING, AND PARTICIPANTS Randomized, double-blind, placebo-controlled clinical trial at an institutional referral center among a sample of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…In standard rhinoplasty procedures, the trauma of fracturing nasal bones and the injuries to angular vessels that cross the osteotomy sites lead to prolonged postoperative periorbital edema and ecchymosis and can affect the cosmetic results and patient's social life. 44 Recent studies have demonstrated that clinical outcomes in patients who undergo otolaryngologic-head and neck surgery may be improved using different surgical approaches, such as the piezoelectric surgery. 45,46 In addition, nonpharmacologic and pharmacologic interventions have been widely used to reduce periorbital edema and ecchymosis after facial plastic surgeries, but evidence for efficacy is conflicting.…”
Section: Discussionmentioning
confidence: 99%
“…In standard rhinoplasty procedures, the trauma of fracturing nasal bones and the injuries to angular vessels that cross the osteotomy sites lead to prolonged postoperative periorbital edema and ecchymosis and can affect the cosmetic results and patient's social life. 44 Recent studies have demonstrated that clinical outcomes in patients who undergo otolaryngologic-head and neck surgery may be improved using different surgical approaches, such as the piezoelectric surgery. 45,46 In addition, nonpharmacologic and pharmacologic interventions have been widely used to reduce periorbital edema and ecchymosis after facial plastic surgeries, but evidence for efficacy is conflicting.…”
Section: Discussionmentioning
confidence: 99%
“…These techniques are difficult to learn, teach, quantify, or duplicate. They are a learned set of skills that come from watching, assisting, and performing rhinoplasties 9 . However, 3D planning can eliminate some of the guesswork for surgeons by simplifying and replicating certain surgical steps that have been more conceptual than physical.…”
Section: Discussionmentioning
confidence: 99%
“…Patients were photographed one week after surgery and the results were evaluated by five plastic surgeons. The results identified that periorbital edema and ecchymosis developments on the seventh day after surgery were much lower in the group that had received intravenous dexamethasone than in the control group [ 27 ].…”
Section: Previous Research Associated With Relevant Dexamethasone Usagementioning
confidence: 99%